Implementasi Program Jakprenuer Dalam Upaya Meningkatkan Perekonomian Umkm Di Masa Pandemi Covid 19 (Studi Kasus Di Kecamatan Tanjung Priok Kota Administrasi Jakarta Utara) - Iyas Nur Hakim; Dody R Setiawan; Mohammad Sofyan (Jurnal Ilmu Administrasi Publik, 2021)
DKI Jakarta as one of the axis of national economic growth is certainly in the spotlight in economic development, one of which is in the growth sector of Micro, Small and Medium Enterprises (MSMEs). The provincial government of DKI Jakarta is committed to developing Micro, Small and Medium Enterprises (MSMEs) in the midst of the people of the capital. Integrated Entrepreneurship Program was initiated more than two years ago, and continues to be developed according to the dynamics of the MSME industry and market needs, where it listens to the aspirations of entrepreneurs. Present with the new brand called Jakprenuer, this program is expected to be a platform for creation, facility and collaboration  for  the  development  of  MSMEs  through  the  entrepreneurship ecosystem, such as start-ups, educational institutions and financing institutions. This study aims to determine the implementation of the Jakprenuer program as an effort to improve the economy of MSMEs in Tanjung Priok District during the Covid-19 pandemic, as well as identify obstacles that arise and the efforts made to overcome them.This   descriptive   research   used   a   qualitative   method   based   on   the implementation theory of Edward III. Data were obtained through direct interviews with informants. The results of the study show that the implementation of the Jakprenuer program has been going well, although there are still some obstacles that must be overcome.